Demonstration by electron microscopy of pili on Gardnerella vaginalis. Issue 6 (December 1984) - Johnson, A P; Davies, H A
Abstract : Eight strains of Gardnerella vaginalis were examined by electron microscopy for the presence of pili. Narrow pili ranging from 3.0 to 7.5 nm in diameter were seen on bacteria from five of the strains studied.